What Caused the Bank Capital Build-up of the 1990s? - Flannery, Mark J.; Rangan, Kasturi P. (Review of Finance, 2008)
Abstract Large U.S. banks dramatically increased their capitalization during the 1990s, to the highest levels in more than 50 years. We document this buildup of capital and evaluate several potential motivations. Our results support the hypothesis that regulatory innovations in the early 1990s weakened conjectural government guarantees and enhanced bank counterparties' incentives to monitor and price default risk. We find no evidence that a bank holding company's (BHC's) market capitalization increases with its asset volatility prior to 1994. Thereafter, the data display a strong cross-sectional relation between capitalization and asset risk.